1922
DOI: 10.1007/bf01884149
|View full text |Cite
|
Sign up to set email alerts
|

Über hormonale Sterilisierung weiblicher Tiere durch subcutane Transplantation von Ovarien trächtiger Weibchen

Abstract: Mit 3Textabbildungen.(Ausgeftihrt mit Unterstfitzung der Rockefe]]er-Stiftun~o'.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

1926
1926
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…He reported this in the Münchner Medizinische Wochenschrift [2], then a part of Pflügers Archiv (for [3], and caused much scientific interest. His observations were surprisingly simple, and thus were sometimes referred to as "the egg of Columbus".…”
Section: Summary Ludwig Haberlandtmentioning
confidence: 96%
See 1 more Smart Citation
“…He reported this in the Münchner Medizinische Wochenschrift [2], then a part of Pflügers Archiv (for [3], and caused much scientific interest. His observations were surprisingly simple, and thus were sometimes referred to as "the egg of Columbus".…”
Section: Summary Ludwig Haberlandtmentioning
confidence: 96%
“…After he committed suicide, on 22 July 1932, scientific discussion about hormonal contraception ceased until 1970 when scientists began referring to his earlier medical and scientific work. Between 1909 and 1931 Ludwig Haberlandt published a total of 134 scientific papers and presentations, only 14 of which were publications dealing with "hormonal contraception of the female organism" [2][3][4][5]. His primary scientific interest was in heart physiology.…”
mentioning
confidence: 99%
“…Alles schien nun optimal, doch der frühe Tod der Mutter warf 1911 einen dunklen Schatten auf die Berliner Zeit, die er retrospektiv als "erlebnisschweres und arbeitsreiches Berliner Jahr" beschrieb [1]. Es zog ihn weg aus der lauten Großstadt und dem großen Institut, an eine kleine reichsdeutsche Universität, um "… seine Höchstleistungen unter möglichst geringen äußeren Hemmungen ausführen zu können …" [1] [9,10] (▶ Abb. 3).…”
Section: Kurzer Lebenslaufunclassified
“…As regards the inhibition of oestrus, Haberlandt (256) found that the graft of a third ovary into a normal rabbit caused prolonged inhibition of ovulation. Subsequent examination of the graft showed that no corpora lutea were present, but that the interstitial tissue, as is usual in such grafts, was highly developed.…”
Section: {E) Maintenance Of Pregnancymentioning
confidence: 99%